Experiences of pain communication in endometriosis: A meta‐synthesis - Nastasja Robstad; Anita Paulsen; Ingvild Vistad; Alexandra Christine Hott; Kari Hansen Berg; Anita Øgård‐Repål; Jannicke Rabben; Eirunn Wallevik Kristoffersen; Gudrun Rohde (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Endometriosis is the leading cause of chronic pelvic pain among women. The pain associated with endometriosis significantly impacts various aspects of patients' quality of life. A notable void in the literature is the absence of a systematic review exploring pain communication between patients with endometriosis and healthcare professionals. Hence, the aim of this qualitative systematic review was to synthesize findings on how patients with endometriosis experience communicating with healthcare professionals about pain and how healthcare professionals experience these interactions. Material and Methods A systematic literature search was conducted related to patients with endometriosis and pain communication in CINAHL PLUS with full text and MEDLINE (via EBSCO host) on May 12, 2023, and updated January 26, 2024. Searches were supplemented by backward searching reference lists and forward searching citations of included reports in Scopus and Google Scholar. The review was guided by the four‐step meta‐synthesis methodology by Sandelowski and Barosso. Critical appraisal of included studies was conducted using Critical Appraisal Skill Program (CASP). Findings were analyzed thematically, using the approach described by Thomas and Harden. The meta‐synthesis was based on a registered protocol in PROSPERO (CRD 42023425430), and the study is reported adhering to the PRISMA 2020 checklist. Results Overall, 37 reports published from 2003 until 2023 contributed to the review, including 4842 participants. Through thematic analysis, we developed the following themes: “Navigating the double burden,” “Lack of mutual understanding,” and “The complexities of conveying pain.” Conclusions The communication of pain between patients with endometriosis and healthcare professionals is complex, encompassing patterns of disbelief, normalization, and psychological attribution. Engaging in discussions about pain presents diverse challenges stemming from insufficient communication skills and assessment tools. Further research is warranted to comprehensively explore the perspectives of both patients and healthcare professionals, aiming to devise strategies that enhance communication and patient care.